Independent Curriculum Practices in the Learning System in Junior High Schools - Indramahdi; Wirman Hanizon; Febriani, Afifah; Guspita, Rosi (Ahlussunnah: Journal of Islamic Education, 2024)
The Merdeka Curriculum (Independent Curriculum) is a curriculum implemented by the Indonesian Ministry of Education, Research, and Technology since 2022. Although this curriculum aims to improve the quality of education in Indonesia, several problems have been identified in its implementation. Therefore, this study aims to analyze the implementation of the Merdeka Curriculum in Islamic jurisprudence (Fiqh) at a junior high school. This study used a qualitative case study method. Data were collected through in-depth interviews with ten informants, including the principal, vice principal for curriculum, teachers, and students. All data were analyzed using the thematic interactive model of data analysis of Miles and Huberman. The research findings describe how the Merdeka Curriculum is implemented in Islamic jurisprudence (Fiqh) through three stages: i) planning by teachers, ii) learning implementation, including opening, core, and closing activities, and iii) evaluation of student outcomes. Overall, all stages have been implemented successfully through the concept of independent learning in the practice of the Merdeka Curriculum.